Residual Stresses 2016 2016
DOI: 10.21741/9781945291173-39
|View full text |Cite
|
Sign up to set email alerts
|

Residual Stress Analysis in Girth-welded Ferritic and Austenitic Steel Pipes Using Neutron and X-Ray Diffraction

Abstract: Abstract. This paper is dedicated to the thorough experimental analysis of the residual stresses in the vicinity of tubular welds and the mechanisms involved in their formation. Pipes made of a ferriticpearlitic structural steel and an austenitic stainless steel are each investigated in this study. The pipes feature a similar geometry and are welded with two passes and comparable parameters. Residual strain mappings are carried out using X-ray and neutron diffraction. The combined use of both techniques permit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Here, the XRD measurements on the inner surface of pipe sections yield different results than the ND measurements on intact pipes for both the original residual stresses after welding, see also [19], and the residual stress state after loading. In both cases, the ND measurements prove that the highest axial and hoop residual stresses occur in the weld metal or at the weld root notch, whereas the XRD measurements underestimate these stresses due to a relaxation effect occurring during the sectioning process.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Here, the XRD measurements on the inner surface of pipe sections yield different results than the ND measurements on intact pipes for both the original residual stresses after welding, see also [19], and the residual stress state after loading. In both cases, the ND measurements prove that the highest axial and hoop residual stresses occur in the weld metal or at the weld root notch, whereas the XRD measurements underestimate these stresses due to a relaxation effect occurring during the sectioning process.…”
Section: Discussionmentioning
confidence: 76%
“…It has been shown that the pipe geometry and the heat input are the governing factors for the residual stress development [15,16], apart from material parameters. The characterization of the welding residual stresses in the pipe welds analyzed in the current paper has already been carried out by the authors [17][18][19], using mainly X-ray and neutron diffraction. It was found that the circumferential contraction of the weld and the highly heated areas in its vicinity during cooling is constrained by the adjacent material, thus causing tensile hoop residual stress in the former and compressive hoop residual stress in the latter areas.…”
Section: Introductionmentioning
confidence: 99%
“…The Second Generation Neutron Residual Stress Mapping Facility (NRSF2) within the High Flux Isotope Reactor (HFIR) is typically employed for bulk residual stress mapping of engineering materials (Hempel et al, 2016) and the Nanoscale Ordered Materials Diffractometer (NOMAD) at the Spallation Neutron Source (SNS) is typically employed for Pair Distribution Function (PDF) analysis of liquids and amorphous solids (Neuefeind et al, 2012). The goal of this study is to demonstrate that both of these instruments can be used to measure texture reliably.…”
Section: Motivationmentioning
confidence: 99%